Asthma control in adolescents: the importance of assessing adherence - Ciprandi, Giorgio; Licari, Amelia; Castagnoli, Riccardo; Ciprandi, Riccardo; Marseglia, Gian Luigi (Acta Biomedica Atenei Parmensis, 2022)
Background Asthma control is the goal of the management, but some patients do not achieve adequate control. Adherence to prescriptions is a relevant factor in this issue. As very few studies addressed this problem in adolescents, we investigated this aspect in this setting. Methods This cross-sectional study consecutively enrolled 87 adolescents (60 males, 27 females, median age 14.2 years) with asthma visited at a third-level pediatric clinic. We used two questionnaires: Morisky Medication Adherence Scale (MMAS-8) and TAI. Results As regards MMAS-8, 23 (26.6%) adolescents had low adherence, 34 (39%) medium, and 30 (34.4%) high. Concerning TAI, 34 (39%) had low adherence, 43 (49.5%) medium, and 10 (11.5%) high. After stratification per asthma control grade, adolescents with partly-controlled asthma had the highest scores for medium adherence (p=0.0017 and 0.049, respectively for MMAS-8 and TAI). Conclusions Adolescents with asthma have poor adherence independently to the asthma control grade. This failure implicates that more attention should be paid to this issue in clinical practice.